Screened potential risk factors for autism and autistic behaviour in children. Literature review - Nowak, Gabriela; Sztybór, Mateusz; Momot, Karol; Kapica, Marcin; Żmijewska, Aleksandra; Krzyżanowska, Maria; Maleszewska, Monika; Piątkiewicz, Julia; Wojtas, Mikołaj; Głogowska, Karen (Journal of Education, Health and Sport, 2024)
Introduction and purpose: This publication is a review of research on potential risk factors for the development of autism and autistic behaviour in children. The purpose of this review is to spread knowledge and awareness of autism syndrome disorder. Brief description of the state of knowledge: Autism syndrome disorder is a neurological and developmental brain disorder. It is characterized by problems with social relationships and communication as well as narrow and repetitive behaviours and interests. The causes of autism spectrum disorder are still not fully understood and pose a challenge to modern medicine. Numerous studies find causes in fetal life and the course of pregnancy, genetic conditions and mutations, environmental risk factors or vaccination. Many theories about the causes of autism require more extensive and thorough research, for which some beliefs have been overturned, such as the search for links between autism spectrum disorder and childhood vaccination. At this point, the role of genetic mutations in the occurrence of autism in children can be confirmed with certainty. Causes are particularly looked for in fetal life and prenatal factors. One theory relates to the activation of the mother's immune system, her production of cytokine and pro-inflammatory factors that affect the development of the fetal nervous system. Results and conclusions: In our review, we aim to present the risk factors that can most significantly influence the development of ASD. These factors include genetics, prenatal diet, smoking during pregnancy, maternal intake of antidepressants, infections during pregnancy, other pregnancy and maternal factors, parental age, various paternal risk factors, lack of breastfeeding, and environmental factors. Some factors need more research for a comprehensive understanding, while others, like breastfeeding and non-smoking during pregnancy, are well-studied and require promotion to reduce the risk of the disorder.